Perancangan Pengalaman Pengguna Aplikasi Personal Shopper menggunakan Metode Human-Centered Design - Febryana Roma Uli Marpaung; Riswan Septriayadi Sianturi; Agi Putra Kharisma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Personal shopper services or buying and selling services are systems individuals offer to